EDUCATIONAL INTERACTION BETWEEN TEACHER AND STUDENT ON KH. HASYIM ASY’ARI’S PERSPECTIVE IN ADABUL ‘ALIM WAL-MUTA’ALLIM CLASSICAL BOOK - fadlillah fadlillah (FALASIFA : Jurnal Studi Keislaman, 2023)
In the world of education, a discourse about teachers and students is a study theme that is always interestingand current. This research is related to the educational interaction between teachers and students from KH.Hasyim Asy’ari’s perspective. Hasyim Asy’ari as stated in the book of Adabul ‘Alim wal-muta’allim. The approachused in this research is descriptive qualitative, this type of research takes the form of library research withcontent analysis used as the analytical tool. The results of the author’s analysis of the book of Adabal ‘Alim waal-Muta’allim, KH. Hasyim Asy’ari really emphasizes the importance of ethics in student interactions withteachers and vice versa. In fact, he quoted the words of the Prophet and the Ulama to emphasize the importanceof moral positions in teachers and students interactions by saying that all good deeds diniyyah (religion), boththose of the heart (my heart) or bodily, or of a nature Qauliyyah and fi’liyyahis not considered or has no value unlessit is surrounded/surrounded/adorned with good and noble morals, the key to success in the teaching andlearning process can only be produced if there is educational interaction (two-way communication) betweenteachers and students and it takes place well and harmoniously in accordance with the rules and mechanismsin the process of teaching and learning activities that are based on morals. There are several values or interactionpatterns that can be developed to create educational interactions between students and teachers from Kh.Hasyim Asy’ari’s perspective, including:Tazkiyatun Nafs, al-ikhlash, attarahum, attawadud, al-I’tina’ (care, attention),al adl or non-discriminatory, al-ijlal Watta’dzim, ash-shabr, and always maintain behavior and ethics and alwayspray for his students and/or teachers.